ChemInform Abstract: Structure and Properties of Magnetoelectric Gallium Ferrite: A Brief Review. Issue 28 (June 2016) - Roy, Amritendu; Mukherjee, Somdutta; Gupta, Rajeev; Prasad, Rajendra; Garg, Ashish
Abstract: Review: 40 refs.